Pengaruh Metode Everyone Is A Teacher Here Terhadap Hasil Belajar Siswa Sds IT Rabbani - Rezki Wahyuni; Rosmalah Rosmalah; Makmur Nurdin (Universtas Negeri Makassar, 2023)
This research is a quantitative research with a research designquasi experiment which aims to before and after using the ETH method and knowing whether or not there is a significant effect of using the ETH method on social studies learning outcomes of fifth grade students of SDS IT Rabbani, Tanete Riattang District. Bone District. .Independent Sample T-test. Based on the results of inferential statistical analysis shows the value oft-count (3,237) is greater (>) valuettable (1.67528) at a significance level of 5%. Thus Ho is rejected and H1 received. From the results of the study, it was concluded that there was a significant difference in the use of the ETH method on social studies learning outcomes for fifth grade students of SDS IT Rabbani, Tanete Riattang District, Bone Regency.